Hungary: Regulation of Sustainable Fiscal Policy in Hungary - Nagy, Zoltán (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter presents and analyses the issue of sustainable fiscal management, focusing on the Hungarian budget. Sustainable fiscal management is closely linked to the principles of the European Union (EU); to this end, fiscal policy focuses on the issues of budget deficit and public debt. Adopting this perspective, this chapter presents the Hungarian fiscal framework and examines the rules and institutions that ensure the implementation of EU principles. As the debt of local governments forms part of public debt, the chapter analyses the issue of local government management, demonstrating the limits of excessive indebtedness. Fiscal policy must respond to economic changes; thus, this chapter also describes the fiscal policy instruments used during the economic crisis, which can be applied in accordance with the budgetary rules for dealing with exceptional situations. Keywords: budget, public debt, budget deficit, sustainable fiscal management, crisismanagement